Performance Management of Police Officers in Tagum City, Davao del Norte: Basis for an intervention program - Russel Aporbo; Rene Chuan; Ellie Chuan (East Asian Journal of Multidisciplinary Research, 2023)
This quantitative study explores the performance management of police officers in Tagum City, Davao del Norte, Philippines. Through random sampling, researchers distributed the research questionnaire to 300 police officers in the research locale. Four indicators were identified for performance management: planning, organizing, leading and controlling with a mean rating of 4.42 or very high for controlling with a standard deviation of 0.29. Organizing got 4.28 with a standard deviation of 0.48; leading has 4.27 or high with a standard deviation of 0.52; and 4.23 or high for planning with a standard deviation of 0.44. The matrix activity is provided that shows the system of activities, key result areas, objectives, strategies/activities, expected outcome, and persons involved. Many factors impact the effectiveness of an organization's performance management system, but three are most important; First, the system must be aligned with and support the organization's direction and critical success factors; second, well-developed, efficiently administered tools and processes are needed to make the system user-friendly and well received by organizational members; and third, and most importantly, managers and employees must use the system in a manner that brings visible, value-added benefits in performance planning, development, feedback, and achieving results.